Effectiveness of group interpersonal psychotherapy for decreasing aggression and increasing social support among Chinese university students: a randomized controlled study - Li, Yutong; Roslan, Samsilah; Ahmad, Nor Aniza; Omar, Zoharah; Zhang, Linyu (Elsevier, 2019)
Background: The objective of this randomized controlled experimental study was to determine the intervention effect of group interpersonal psychotherapy (G-IPT) for aggression and social support among Chinese first-grade university students. Methods: Through stratified random sampling, 1469 students, aged 18–19 years, were enrolled. Participants whose score achieved the aggressive evaluation standard were selected and then 60 participants were randomly divided into 2 groups: G-IPT and control. The participants in the G-IPT group received 16 sessions of treatment, whereas the participants in the control group did not receive any intervention. All participants completed the assessment three times: before, after, and tracking. Results: The results showed that the total score and the scores of all subscales of aggression dropped significantly (P < 0.01). Also, the total score and the scores of objective support and utilization degree of social support increased significantly (P < 0.05). Conclusion: G-IPT was effective in treating aggression and improving social support level, and the effect was stable.